From Cinderella to Stepford Wife ? about the Archetypal and Disney Model of Fairytale Femininity - Pilawska, Roksana (INSTED: Interdisciplinary Studies in Education & Society, 2018)
In the article I made an attempt to describe the American ideology of way of life, the manifestations ofwhich are visible in the animated productions mentioned above. I have also characterized the notion of Disneyfication, commonly used in the subject literature, which refers to the manner of transforming originalliterary fairy tales characteristic of a corporation, so that they are immediately recognized and equated withthe label by all recipients. The examples of literary fairy tales and their famous fairytale adaptations presented by me prove that original fairytale stories, filled with archetypal figures of virtuous princesses andbrave knights for centuries playing an important role in the process of socialization and cultural adaptation ofthe new generation, perpetuated socially accepted norms, principles and values, and their later animated adaptations only underlined their socializing dimension. Both versions, despite feature and axiological differences, have one denominator ? in a similar way they create a schematic model of women?s characters. When interpreting selected tales and film productions based on them, I wanted to show that the contemporary search for the philosophical stone of disney animation in the form of a hidden, chauvinistic messagegoing beyond the original meaning of the tale itself seems to be over-interpreted.